Superconducting properties of yba2cu3o7−δ with a multiferroic addition synthesized by a capping agent-aided thermal treatment method - Che Dzul-Kifli, Nur Athirah; Awang Kechik, Mohd Mustafa; Baqiah, Hussein; Shaari, Abdul Halim; Lim, Kean Pah; Chen, Soo Kien; Abd Sukor, Safia Izzati; Shabdin, Muhammad Kashfi; Abdul Karim, Muhammad Khalis; Mohd Shariff, Khairul Khaizi; Miryala, Muralidhar (Multidisciplinary Digital Publishing Institute, 2022)
A bulk YBa2Cu3O7−δ (Y-123) superconductor synthesized by a thermal treatment method was added with different weight percentages (x = 0.0, 0.2, 1.0, 1.5, and 2.0 wt.%) of BiFeO3 (BFO) nanoparticle. X-ray diffraction (XRD), alternating current susceptibility (ACS), and field emission scanning electron microscopy (FESEM) were used to determine the properties of the samples. From the XRD results, all samples showed an orthorhombic crystal structure with a Pmmm space group. The sample x = 1.0 wt.% gave the highest value of Y-123. The high amounts of BFO degraded the crystallite size of the sample, showing that the addition did not promote the grain growth of Y-123. From ACS results, the Tc-onset value was shown to be enhanced by the addition of the BFO nanoparticle, where x = 1.5 wt.% gave the highest Tc value (91.91 K). The sample with 1.5 wt.% showed a high value of Tp (89.15 K). The FESEM analysis showed that the average grain size of the samples decreased as BFO was introduced. However, the small grain size was expected to fill in the boundary, which would help in enhancing the grain connectivity. Overall, the addition of the BFO nanoparticles in Y-123 helped to improve the superconducting properties, mainly for x = 1.5 wt.%.